Improving the Quality Of Education Through The Application of Students Centered Learning: A Theoretical Review - Novita Anggraeni (Green Publisher Indonesia, 2021)
This study aims to describe the application of student-centered learning to improve the quality of education. The results of this study show how the application of student-centered learning has an increase in improving the quality of education, namely: (1) one of factors that can improve the quality of education that must be done is